The effects of kicking leg preference on the bilateral leg strength asymmetries of amateur football players - Yildiz, M.; Kale, M. (Isokinetics and Exercise Science, 2018)
OBJECTIVE: To determine the effects of kicking leg preference on the bilateral leg strength asymmetries of amateur football players. METHODS : Thirty-four right-dominant (RD) and twenty-three left-dominant (LD) amateur football players volunteered to participate in the study. Squat and countermovement jump, standing long jump, and isokinetic knee strength (at 60, 180 and 300 ° /s) were tested with respect to inter-limb asymmetry index (ASI). RESULTS: There were significant differences in horizontal jump and H/Q ratio at 60 ° /s between DL and NDL in all football players. There were also significant differences in standing long jump, hamstring peak torque at 180 ° /s and H/Q ratio at 60 ° /s in the LD football players (p < 0.05). Moreover, the LD group had greater percentage of subjects with ASI > 15% for standing long jump, hamstring peak torque at 180 ° /s. Furthermore the percentage of subjects with H/Q Ratio < 0.60 for 60 ° /s was greater in the LD players` DL. CONCLUSION: Bilateral leg strength asymmetries may be affected by a single leg predominantly in the mobilization workouts. Having higher inter-limb asymmetry index, LD players may be screened and trained to minimize leg strength asymmetries.